Chimeric design of pyrrolysyl-tRNA synthetase/tRNA pairs and canonical synthetase/tRNA pairs for genetic code expansion - Ding, Wenlong; Zhao, Hongxia; Chen, Yulin; Zhang, Bin; Yang, Yang; Zang, Jia; Wu, Jing; Lin, Shixian (Nature communications, 2020)
An orthogonal aminoacyl-tRNA synthetase/tRNA pair is a crucial prerequisite for site-specific incorporation of unnatural amino acids. Due to its high codon suppression efficiency and full orthogonality, the pyrrolysyl-tRNA synthetase/pyrrolysyl-tRNA pair is currently the ideal system for genetic code expansion in both eukaryotes and prokaryotes. There is a pressing need to discover or engineer other fully orthogonal translation systems. Here, through rational chimera design by transplanting the key orthogonal components from the pyrrolysine system, we create multiple chimeric tRNA synthetase/chimeric tRNA pairs, including chimera histidine, phenylalanine, and alanine systems. We further show that these engineered chimeric systems are orthogonal and highly efficient with comparable flexibility to the pyrrolysine system. Besides, the chimera phenylalanine system can incorporate a group of phenylalanine, tyrosine, and tryptophan analogues efficiently in both E. coli and mammalian cells. These aromatic amino acids analogous exhibit unique properties and characteristics, including fluorescence, post-translation modification. Orthogonal aminoacyl-tRNA synthetase/tRNA pairs are crucial for the incorporation of unnatural amino acids in a site-specific manner. Here the authors use rational chimera design to create multiple efficient pairs that function in bacterial and mammalian systems for genetic code expansion.